Regional correlation of the Lesser Himalayan and Tethyan basin sediments of Kali valley, Indo-Nepal area - Tewari, V. C. (Journal of Nepal Geological Society, 1998)
The Uttarakhand Lesser Himalaya of India (Kumaon-Garhwal basins) is the most important central sector of the Himalayan arc between Kali River, Nepal in the east and Tons River, Himachal in the west. The Lesser Himalayan sedimentary belts are bound by the Main Boundary Thrust (MBT) in the south and Main Central Thrust (MCT) in the north in Indo-Nepal border across the Kali River. The revised biostratigraphy, carbon isotope and event stratigraphy has established a Mesoproterozoic age for the Deoban belt and Lower Cambrian age for the Krol-Tai belt in the Indian part. Identical sedimentary facies and stromatolites are found in western Nepal across the Kali River (Kali-Gandaki Group) and is in fact the extension of the Indian Lesser Himalaya (Deoban-Tejam belt) into western Nepal. The Tethyan sedimentary zone is separated from the Central Crystallines in the north of the Lesser Himalaya of Indo-Nepal region by Tethyan Thrust/Malari Thrust/frans-Himadri Thrust. Recent fossil finds, sedimentological and carbon isotopic signatures from Ralam, Garbyang, Shiala and Yong formations indicate continuous sedimentation from Terminal Proterozoic to Silurian period. The Precambrian/ Cambrian boundary is tentatively placed within the Garbyang Formation. A detailed correlation of the Lesser and Tethyan Himalayan sedimentary belts of the lndo-Nepal border region across the Kali River is attempted and discussed in this paper.